Opinions and Views of Slovenian and Croatian Preschool Teachers on Their Ability to Identify Potentially Gifted Preschool Children - Gomerčić, Ljiljana (Revija za elementarno izobraževanje, 2022)
This research aims to investigate the differences between Slovenian and Croatian preschool teachers in their opinions and views on the identification of potentially gifted children, on the self-assessment of their professional skills in this field, on the importance of education and professional formation, and on the role of school counseling service and children’s parents. The survey included 542 participants, 248 (45.8%) preschool teachers from Slovenia and 294 (54.2%) preschool teachers from Croatia. The results show that there are statistically significant differences in self-assessment of individual professional skills between Slovenian and Croatian preschool teachers.
Keywords: potentially gifted children, preschool child, preschool education, professional competence, preschool educator